2020
DOI: 10.1093/pubmed/fdaa139
|View full text |Cite
|
Sign up to set email alerts
|

Variations in newspaper reporting of suicidal behavior in the WHO–South-East Asian region

Abstract: Background South-East Asia is a densely populated region, comprising of 11 low- and middle-income countries and contributing to 39% of global suicides. There are serious challenges to suicide prevention in the region such as lack of high-quality suicide data, underreporting and poor quality of media reporting. The current report aimed to assess the variations in newspaper reporting of suicidal behavior in the World Health Organization–South-East Asian countries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
13
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 21 publications
5
13
1
Order By: Relevance
“…A comparable form of news presentation was reported in other parts of countries like India (Menon et al, 2020). Recent reviews from WHO-South-East Asia also reported a nearly similar finding of media reporting in LMICs of the region (Arafat et al, 2020b(Arafat et al, ,2020c. Other studies also reported poor adherence in Bangladesh (Arafat et al, 2020d(Arafat et al, , 2019, China (Chu et al, 2018), Thailand (Marthoenis et al, 2020), and Indonesia (Nisa et al, 2020).…”
Section: Discussionsupporting
confidence: 63%
“…A comparable form of news presentation was reported in other parts of countries like India (Menon et al, 2020). Recent reviews from WHO-South-East Asia also reported a nearly similar finding of media reporting in LMICs of the region (Arafat et al, 2020b(Arafat et al, ,2020c. Other studies also reported poor adherence in Bangladesh (Arafat et al, 2020d(Arafat et al, , 2019, China (Chu et al, 2018), Thailand (Marthoenis et al, 2020), and Indonesia (Nisa et al, 2020).…”
Section: Discussionsupporting
confidence: 63%
“…[ 10 ] However, wide variations have also been reported among studies based on both inter- and intra-country. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…A recent review from WHO-South-East Asia also reported nearly similar finding of media reporting in LMICs of the region . Other studies also reported the poor adherence in Bangladesh (Arafat et al, 2019;Arafat, Mali, et al, 2020), China (Chu et al, 2018), India (Arafat, Menon, et al, 2020;Menon et al, 2020), and Indonesia (Nisa et al, 2020).…”
Section: Discussionmentioning
confidence: 94%